Penerapan Metode Waterfall Untuk Perancangan Sistem Inventory Pada PT.Raih Usaha Karya Mandiri - Azmi, Khairul; Nurdin, Fahril (Jurnal Teknologi Komputer dan Informasi, 2024)
The inventory system is a crucial component for companies to facilitate the process of recording goods and generating reports in a structured, controlled, systematic, and interconnected manner. At PT Raih Usaha Karya Mandiri, the recording of goods entering and exiting the warehouse is still done manually, using a logbook form. This often leads to recording errors and data mix-ups, hindering access to information when needed. To address this issue, a web-based inventory system was developed using the waterfall system development method, which operates sequentially. The system was designed using a MySQL database and PHP programming language. The implementation results indicate that the developed inventory system simplifies the recording of goods movement, enhances stock data accuracy, and accelerates the process of creating inventory reports, there by supporting the work efficiency of PT Raih Usaha Karya Mandiri employees.